Diplomacy : a very short introduction - Siracusa, Joseph M. (Joseph Marcus) (Oxford : Oxford University Press, 2010)
The course and consequences of major events of modern international diplomacy have shaped and changed the global world in which we live. Joseph M. Siracusa introduces the subject of diplomacy from a historical perspective, providing examples from significant historical phases and episodes to illustrate the art of diplomacy in action.
Includes bibliographical references (p. 125-133) and index.
Keywords: Diplomacy; Diplomacy -- History